Impact of cessation of caffeine citrate therapy on intermittent hypoxemia patterns among preterm infants born before 34 weeks - Mashep, Peter Kipkurui; Ochieng, Roseline; Coleman, Jesse; Waiyego, Mary; Ginsburg, Amy Sarah; Chomba, Dorothy; Ondieki, Morris Ogero; Irimu, Grace; Macharia, William M.; Ansermino, J. Mark (Frontiers in Pediatrics, 2025)
IntroductionIntermittent hypoxemia (IH) is defined as oxygen saturation (SpO2) drop ≥5% from the baseline (set at 90 s preceding the event) to a level less than 90% lasting for ≥5 s. Caffeine citrate, the standard of care for apnea of prematurity, reduces IH events. IH contributes to both short and long-term adverse neurologic outcomes. Standard patient monitors cannot detect IH events due to long averaging times.ObjectiveDescribe change in patterns of IH events in preterms <34 weeks before and after cessation of caffeine citrate and factors associated.MethodsInterrupted time series study design. Data was collected from 1 December 2022 to 30 June 2023. MASIMO RAD-G oximeter was used, and analysis done using Trace software V3028 output was desaturation frequency, duration, and time. Data exported, stored, and analyzed using Excel 2016. Change in slope compared visually in two time periods interrupted at 34 weeks and objective statistical analysis done using the Student-T-test, CI 95% with p-value <0.05 considered significant.Results49 patients medical records available for secondary analysis. Frequency of IH events increased from 7.94 to 40.94 events/hour (5-fold). IH events of durations lasting between 0 and 10 s, and >20 s decreased by 12.3% and 6.8%, respectively, while those lasting 10–20 s increased by 17%. The mildly severe IH events decreased by nearly half, 46.9% (78.4% to 31.5%), while both the moderately severe and severe IH events increased by 17.4% (18.5%–35.9%), and 26% (6.7% to 32.7%) respectively. The time spent in hypoxemia increased by 2.3 h/week/patient, while the cumulative time in hypoxemia increased by 1.6 h/patient. Preterms exposure to ACS (antenatal corticosteroids) was associated with decrease in IH events.ConclusionCaffeine citrate cessation leads to worsening of IH events with increased frequency, duration, severity and cumulative time spent in hypoxemia. Exposure to ACS was associated with decrease in IH events.RecommendationCaffeine citrate therapy use beyond 34 weeks is likely to be beneficial especially in the context of LMIC where antenatal steroid is not always administered, and monitoring of preterm babies is suboptimal. Safe cessation of caffeine therapy requires monitoring to detect IH events.